Assessment of anxiety disorders in students starting work with coronavirus patients during a pandemic in Podlaskie Province, Poland - Czorniej, Klaudia Paula; Krajewska-Kułak, Elzbieta; Kułak, Wojciech (Frontiers in Psychiatry, 2022)
Background Anxiety disorders are considered the sixth most important factor resulting in non-fatal health loss in the world. Moreover, they are among the first ten causes of years lived with disability (YLD) across the globe. Important clinical disorders include e.g., panic disorder, social anxiety disorder, generalized anxiety disorder and specific phobia. Objectives The study aimed to analyse the occurrence of level anxiety in students who start work at the time of the COVID-19 pandemic, with relation to the socio-demographic factors and health status, vaccination, conovirus infection, assistance of a psychologist or psychiatrist in the past, and using tranquilizers. Methods The study involved 255 students from Poland starting work with coronavirus patients during the pandemic. It was conducted using our own questionnaire, the Liebowitz Social Anxiety Scale (LSAS) and the State-Trait Anxiety Inventory (STAI). Results Fifty-one percent of subjects demonstrated symptoms of mild to severe social phobia. Level of trait anxiety among students correlated significantly with age and gender (females). The level of social anxiety in the evaluated students was significantly correlated with marital status, the self-assessment of the experienced fear, self-perceived health status, having had a coronavirus infection, fear of deterioration of one's health after starting work with coronavirus patients, and fear of contracting the disease while working with coronavirus patients, and using tranquilizers. Level of state anxiety significantly correlated with state anxiety, the self-assessment of professional preparedness for work with coronavirus patients, self-perceived health status, vaccination against coronavirus, and the assistance of a psychiatrist in the past. Conclusions The proportion of students showing social anxiety is alarming. Anxiety among the evaluated students during the COVID-19 pandemic was correlated with many factors.